2022
DOI: 10.3390/jmse10111728
|View full text |Cite
|
Sign up to set email alerts
|

Recent Technological and Methodological Advances for the Investigation of Submarine Landslides

Abstract: Submarine landslides have attracted widespread attention, with the continuous development of ocean engineering. Due to the recent developments of in-situ investigation and modelling techniques of submarine landslides, significant improvements were achieved in the evolution studies on submarine landslides. The general characteristics of typical submarine landslides in the world are analyzed. Based on this, three stages of submarine landslide disaster evolution are proposed, namely, the submarine slope instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…In general, evaluating the engineering geology environment requires an on-site investigation, collection of corresponding data (including historical data), and development of an evaluation report (Guzzetti et al 2005;Fell et al 2008;Shano et al 2020;Xie et al 2022;Guo et al 2023b, c;Shan et al 2022;Dong et al 2022Dong et al , 2023. The evaluation report should describe the characteristics of the regional engineering geology environment as well as identify and evaluate geologic disasters and the corresponding mitigation measures (Aurelio 2004).…”
Section: Evaluation Of the Engineering Geology Environmentmentioning
confidence: 99%
“…In general, evaluating the engineering geology environment requires an on-site investigation, collection of corresponding data (including historical data), and development of an evaluation report (Guzzetti et al 2005;Fell et al 2008;Shano et al 2020;Xie et al 2022;Guo et al 2023b, c;Shan et al 2022;Dong et al 2022Dong et al , 2023. The evaluation report should describe the characteristics of the regional engineering geology environment as well as identify and evaluate geologic disasters and the corresponding mitigation measures (Aurelio 2004).…”
Section: Evaluation Of the Engineering Geology Environmentmentioning
confidence: 99%
“…1 Some other comprehensive reviews of numerical modelling for large deformation in geotechnics can be found in Refs. [2][3][4][5] In MPM, the material domain is discretised in material points that can be treated as integration points in FEM. 6 To solve the distorted mesh issue in FEM, the mesh is set to its original position in MPM at each time step, and the material points carry all the permanent information (e.g.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Some other comprehensive reviews of numerical modelling for large deformation in geotechnics can be found in Refs. 2–5…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The Navier-Stokes equation or the shallow-water equation is generally applied to the analysis of debris flow, and FLO-2D (O'Brien et al, 1993), DAN (Hungr, 1995), RAMMS (Christen et al, 2010), r.avaflow (Mergili et al, 2017), and Deb2D (An et al, 2019) are among the representative models. In addition, models that comprehensively analyze landslides and debris flows are being developed and introduced (Hong et al, 2020;Liu and He, 2020;Nian et al, 2021;Shan et al, 2022;Zhou et al, 2022;Wu et al, 2023). In these combined models, the landslide collapse area is calculated through slope stability analysis based on time-varying rainfall data.…”
Section: Introductionmentioning
confidence: 99%